Evaluation of the Risk of Knee Osteoarthritis and Its Predictive Factors with Emphasis on Physical Activity - Parvaneh Shamsipour-Dehkordi; Marzieh Entezari; Robab Sahaf (Vesnu Publications, 2017)
Introduction: Designing programs for the prevention of osteoarthritis of the knee requires an understanding of its risk factors. The aim of the present study was to determine the relationship between the risk of knee osteoarthritis among the elderly and age, body mass index (BMI), education, depression, physical activity, and gender of the elderly. Materials and Methods: The participants consisted of 220 elderly individuals suffering from knee osteoarthritis and 220 healthy elderly individuals. The subjects were selected using voluntary sampling methods. The data collection tools included a demographic characteristics form and the Geriatric Depression Scale (GDS) and International Physical Activity Questionnaire (IPAQ). Results: The relationship of all variables with the risk of knee osteoarthritis was investigated through logistic regression analysis of a progressive model considering odds ratio (OR) and confidence interval (CI). There was a significant relationship between age and gender and the risk of developing osteoarthritis (P < 0.05); women were more susceptible to knee osteoarthritis than men (P < 0.05). The prevalence of overweight and obesity was higher among the elderly with knee osteoarthritis than the healthy subjects. Level of depression had a significant correlation with the risk of knee osteoarthritis (P < 0.05). A significant association was observed between levels of physical activity and the risk of knee osteoarthritis and the number of inactive elderly individuals in the knee osteoarthritis group was higher than the healthy elderly group. With increase in the level of education, the possibility of developing knee osteoarthritis decreased and those with an education level of lower than diploma had a greater chance of developing knee osteoarthritis (P < 0.05). Conclusion: Gender, obesity, depression, lack of physical activity, weight gain, education of lower than diploma, and lack of insight and knowledge were risk factors for susceptibility to knee osteoarthritis.